Logging in Ja`lan Bani Bu Ali: South Sharqiya Governorate – Sultanate of Oman - Al-Balushi, Ali Said Salim (Al-Adab Journal, 2021)
Residents in arid, semi-arid and sub-humid areas significantly depend on natural vegetation for their survival. They use vegetation for herding livestock, coal production, cooking, heating and constructing animal sheds. It is also a nutritional and medical resource for many rural and Bedouin communities. This study aims to investigate the process of logging in Ja`lan Bani Bu Ali region, clarify the factors of its occurrence and its environmental and socio- economic impacts. For fulfilling the goal, the study depends mainly on field work that includes recording observations and field survey of logging sites. The field work covers 32 sites including mountains, adjacent slopes and sandy desert plains. In addition, a questionnaire was designed to qualitatively explore the opinions of more than 40 families involved in logging practices with focusing on their impacts on the surrounding environment. Results of this study showed a set of environmental and socio-economic impacts evolved from logging practices, such as: increasing logging journey to target locations, retreating tree cover, rising timber deficit and the declining biological diversity. The study recommends the cultivation of target species, such as Acacia tortilis،, Prosopis cineraria and Ziziphus spina-christi in order to alleviate the impacts of logging practices and to expand this experimental plantation to reduce the pressure on natural plants.